Graphitic carbon nitride nanosheet-assisted preparation of N-enriched mesoporous carbon nanofibers with improved capacitive performance. (November 2015) - Liang, Qinghua; Ye, Ling; Xu, Qiang; Huang, Zheng-Hong; Kang, Feiyu; Yang, Quan-Hong
Abstract: N-enriched mesoporous carbon nanofibers (NMCNFs) were prepared by an electrospinning technique using graphitic carbon nitride (g-C3 N4 ) nanosheets both as sacrificial template and N-doping source. The resultant NMCNF film has a high N-doping level of 8.6 wt% and a high specific surface area of 554 m 2  g −1 . When directly used as the electrode material for supercapacitor, the free-standing NMPCNF film shows a significantly improved capacitive performance including a higher specific capacitance (220 F g −1 at 0.2 A g −1 ) and a better rate capability (∼70% retention at 20 A g −1 ) than those of microporous carbon nanofiber film prepared using the same process without using g-C3 N4 nanosheets (145 F g −1 at 0.2 A g −1 and ∼45% retention at 20 A g −1 ). Moreover, the NMCNFs show superior stability with only a ∼3% decrease of its initial capacitance after 1000 cycles at a high current density of 10 A g −1 . More significantly, the energy density of a symmetrical supercapacitor (SC) based on the NMPCNF film can reach 12.5 Wh kg −1 at a power density of 72 W kg −1 .